Overexpression of Yes Associated Protein 1, an Independent Prognostic Marker in Patients With Pancreatic Ductal Adenocarcinoma, Correlated With Liver Metastasis and Poor Prognosis. Issue 7 (August 2017) - Salcedo Allende, Maria Teresa; Zeron-Medina, Jorge; Hernandez, Javier; Macarulla, Teresa; Balsells, Joaquim; Merino, Xavier; Allende, Helena; Tabernero, Josep; Ramon y Cajal Agüeras, Santiago
Abstract : Objectives: Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer. Overexpression of Yes associated protein 1 (YAP1), a downstream target of Hippo pathway, implicated in regulation of cell growth and apoptosis, has been reported in several human tumor types. The objective of this study was to investigate YAP1 expression in patients with PDAC and its prognostic values. Methods: We evaluated YAP1 expression in 64 PDAC and 15 chronic pancreatitis (CP) cases and its related pancreatic intraepithelial neoplasia (PanIN) lesions and in 5 control subjects. Yes associated protein 1 expression was determined by immunohistochemistry. Association of YAP1 with clinicopathologic features in PDAC, disease-free survival, and overall survival was analyzed. Results: We found a higher positive rate of nuclear expression of YAP1 in PDAC than in CP ( P = 0.000) and lower expression of YAP1 in PanIN lesions in CP in contrast with expression in PanIN lesions in PDAC. Nuclear overexpression of YAP1 in PDAC is associated with hepatic metastasis ( P = 0.0280) and is a prognostic factor ( P = 0.0320), as well as surgical margin involvement ( P = 0.0013) and tumoral stage ( P = 0.0109). Conclusions: Overexpression of YAP1 may occur as a part of tumorigenesis of PDAC. Yes associated protein 1 is an independent prognostic marker for overall survival of PDAC and associated with liver metastasis, being a potential therapeutic target.